Peningkatan Pengawasan Penyelenggaraan Pelayanan Publik Melalui Saluran Ombudsman di Desa Tuapejat, Kecamatan Sipora Utara, Kabupaten Kepulauan Mentawai - Muhammad Ichsan Kabullah; Ria Ariany; Yoserizal Yoserizal; Wewen Kusumi Rahayu (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2019)
The existence of public services in local governments is facing a severe problem. The implementation of regional autonomy has not been able to encourage the birth of services quickly, cheaply, accountable, and transparently. This is compounded by a slow service culture in the bureaucracy. As a result, the essence of government as a public servant is lost. In that sense, the Ombudsman established since 2008. Based on Law Number 37 of 2008 about the Ombudsman of the Republic of Indonesia, the Ombudsman has a purpose as a bridge between the government and the community in improving public services. In its development, the existence of the Ombudsman is present in areas such as West Sumatra Province. However, there are still many people who have not utilized this institution to its full potential. This article attempts to describe efforts to improve the oversight function of public service delivery through the Ombudsman in Tuapejat Village. The village, located in the Mentawai Islands Regency, is an isolated area in West Sumatra. With the presence of the Ombudsman, it is hoped that public services in the village can improve amid the geographical constraints faced. From the activities carried out, it can be seen that the public is not familiar with the Ombudsman. Community participation in overseeing public service delivery which has been weak so far has also been caused by permissive culture. Therefore, the presence of an ombudsman is felt to be important in increasing public participation in carrying out service supervision in the bureaucracy.